Subpopulations of PKCγ interneurons within the medullary dorsal horn revealed by electrophysiologic and morphologic approach. Issue 9 (September 2015) - Alba-Delgado, Cristina; El Khoueiry, Corinne; Peirs, Cédric; Dallel, Radhouane; Artola, Alain; Antri, Myriam
Abstract : Abstract: Mechanical allodynia, a cardinal symptom of persistent pain, is associated with the unmasking of usually blocked local circuits within the superficial spinal or medullary dorsal horn (MDH) through which low-threshold mechanical inputs can gain access to the lamina I nociceptive output neurons. Specific interneurons located within inner lamina II (IIi ) and expressing the gamma isoform of protein kinase C (PKCγ + ) have been shown to be key elements for such circuits. However, their morphologic and electrophysiologic features are still unknown. Using whole-cell patch-clamp recordings and immunohistochemical techniques in slices of adult rat MDH, we characterized such lamina IIi PKCγ + interneurons and compared them with neighboring PKCγ − interneurons. Our results reveal that PKCγ + interneurons display very specific activity and response properties. Compared with PKCγ − interneurons, they exhibit a smaller membrane input resistance and rheobase, leading to a lower threshold for action potentials. Consistently, more than half of PKCγ + interneurons respond with tonic firing to step current. They also receive a weaker excitatory synaptic drive. Most PKCγ + interneurons express Ih currents. The neurites of PKCγ + interneurons arborize extensively within lamina IIi, can spread dorsally into lamina IIo, but never reach lamina I. In addition, at least 2 morphologically and functionally different subpopulations of PKCγ + interneurons can be identified: central and radial PKCγ + interneurons. The former exhibit a lower membrane input resistance, rheobase and, thus, action potential threshold, and less PKCγ + immunoreactivity than the latter. These 2 subpopulations might thus differently contribute to the gating of dorsally directed circuits within the MDH underlying mechanical allodynia. Abstract : Supplemental Digital Content is Available in the Text.At least 2 functionally and morphologically distinct subpopulations of PKCγ + interneurons coexist in the medullary dorsal horn, which might play different roles in tactile allodynia processing.